Gambaran Stres Kerja pada Perawat di Rumah Sakit Tahun 2025 - Resti Nilam Resmini; Munaya Fauziah (An-Najat, 2025)
Job stress is a problem that always exists and occurs in the world. Job stress is a psychosocial hazard that comes from various sources such as relationships with coworkers, work conditions, and work organizations, especially for nurses who work in hospitals. Because of the high intensity of always meeting and interacting directly with patients and families which is quite difficult and complex, it can be indicated as a trigger for job stress in nurses. This study aims to determine the picture of job stress in nurses in 2025. Using a literature review (Literature study) from the Garuda journal portal using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) with a qualitative approach with sampling using exclusion and inclusion criteria. The level of nurse stress tends to be in the moderate category (60.3%) or mild (55%) in (Khoirunnisa et al.) (Public Health et al., n.d.), (63.3%) in (Izzah Bialfi Hasanah et al). However, research also shows that a percentage of nurses experience severe stress (5%) in Khoirunnisa et al., (10%) in Izzah Bialfi Hasanah et al., and (61.4%) in Anwar et al. This relationship is closely linked to workload, with nurses with heavy workloads tending to experience moderate to severe stress. Similarly, inappropriate or disruptive work shifts are significantly associated with increased stress. Women tend to experience work stress more easily than men due to their dual roles (as nurses and housewives) and their tendency to use emotions when dealing with tasks. Although female nurses are often dominant (56.7% in the emergency department during the pandemic, 45% in outpatient settings), there is significant identification of work stress levels with age, gender, workload, and work shift characteristics. Hospitals are advised to develop psychosocial support programs for nurses, such as open sharing sessions, alternating refreshing activities, or providing counseling. These programs are crucial to helping nurses manage stress.